Astrovirus-associated gastroenteritis in children. Issue 10 (October 1978) - Ashley, C R; Caul, E O; Paver, W K
Abstract : In a small astrovirus-associated outbreak of gastroenteritis in a ward of a local children's hospital two out of five children with symptoms excreted astrovirus particles. No astrovirus particles were found in faeces from the remaining asymptomatic child, and no other viral or bacterial pathogens were found in any of the children. Virus excretion persisted for only a few days. Rising antibody titres to the astrovirus particles were demonstrated in one child, and IgM was also demonstrated in this patient's serum.